OUR EXPERIENCE WITH TOPOTECAN AS SECOND- LINE TREATMENT OF PATIENTS WITH RELAPSED SMALL CELL LUNG CANCER - Deyan Davidov (Peytchinski Publishing, 2010)
Objectives: Single agent intravenous Topotecan is an effective treatment for small cell lung cancer /SCLC/ after failure of first- line chemotherapy. The aim of this study was to evaluate the efficacy and toxicity of intravenous Topotecan in recurrent SCCC. Methods: In the period 2008- 2009 seventeen consecutive patients with relapsed SCLC entered the study. The treatment schedule consists of Topotecan 1,5 mg/m2 i.v. for five consecutive days, with repetition every 21 days. Results: Overall response rate was 23,5%. Median survival was 6,4 months. Nausea, vomiting and neutropenia were most common side effects. Conclusion: Intravenous Topotecan is effective as second- line therapy for patients with relapsed SCCC with good tolerability.